DIGITALISASI PEMBELAJARAN PJOK UNTUK MENINGKATKAN HASIL BELAJAR SENAM AIH - Ramadhan, Javanda Herlyan; Pratama, Dani Slamet; Ratimiasih, Yulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using Canva media in improving learning outcomes of Senam Anak Indonesia Hebat. The research method used was a quantitative method with a Pre-Experimental Design approach, employing a Nonequivalent Control Group Design. The study was conducted at SMAN 1 Tahunan, Jepara Regency. The population consisted of 11 tenth-grade classes. The samples were class X-5 as the experimental class with 36 students and class X-6 as the control class with 36 students. Data collection was carried out using a multiple-choice test consisting of 25 questions. Quantitative data analysis techniques used statistical tests, including prerequisite tests (normality test and homogeneity test) and hypothesis testing using the t-test. The results showed that learning outcomes improved in both classes; however, the improvement in the experimental class was more significant than in the control class. In the control class, the percentage of students in the high category increased from 25% in the pretest to 58.4% in the posttest, while in the experimental class it increased dramatically from 16.7% to 97.2%, with the low category decreasing from 38.9% to 2.8%. Based on the prerequisite tests, the data were normally distributed and homogeneous because all significance values were greater than 0.05 and the Levene’s test result was 0.702 (> 0.05). Furthermore, the t-test result showed a significance value of 0.000 (< 0.05), indicating that H0 was rejected and Ha was accepted. Therefore, it can be concluded that the use of Canva media has a significant effect on improving the learning outcomes of Senam Anak Indonesia Hebat among tenth-grade students at SMAN 1 Tahunan.